A preparation process of high-quality quartz tube
By removing impurities by shot blasting, acid leaching and spin coating, the polyvinylidene fluoride film is covered, and combined with oil bath heating and electrolysis to form a composite material, the problem of decreased purity and unstable film layer of quartz tubes when improving photocatalytic performance is solved. problem, achieving the preparation of quartz tubes with high mechanical strength and efficient photocatalytic performance.
Patent Information
- Application Number
- CN202411622631.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-11-14
AI Technical Summary
When the existing quartz tubes improve photocatalytic performance, they are prone to decrease purity, internal defects and instability of the photocatalyst film layer.
High-purity quartz sand is obtained through shot peening acid leaching combined with impurity removal process, and the inner wall of the quartz tube is covered with a polyvinylidene fluoride film using spin coating method, and then heated in an oil bath under a nitrogen atmosphere to form a passivated black phosphorus dispersion. Finally, a cobalt oxide-molybdenum oxide-black phosphorus composite material is formed through electrolysis.
Improve the mechanical strength and quality of quartz tubes, ensure the stability and efficient performance of the photocatalytic membrane layer, and enhance the optical catalytic degradation capacity of the quartz tube in visible light or ultraviolet light.
Smart Images

Figure CN119143407B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of chemistry and chemical engineering, in particular to a preparation process of a high-quality quartz tube. Background Art
[0002] For the health of citizens, the polluted environment needs to be purified. Photodecomposition and photocatalysis are hot research directions in fields such as materials science and environmental engineering. They can use light energy to trigger chemical reactions, thereby achieving the process of decomposing, transforming or catalyzing pollutants. Quartz materials (especially quartz tubes) are often used as reaction containers or reaction substrates in these applications due to their excellent light transmittance, chemical inertness and high-temperature stability.
[0003] Quartz tube glass is usually composed of pure transparent silicon dioxide. Transparent quartz tube has the problems of high light transmittance, low refractive index and poor light absorption capacity. In order to improve the light absorption range of quartz tube and enhance its photocatalytic performance, the commonly used method is to prepare quartz tube by doping some colorants in high-purity quartz sand, or to attach a layer of photocatalyst to the inner wall of quartz tube to improve the photocatalytic ability. However, doping colorants in high-purity quartz sand can easily lead to a decrease in the purity of quartz tube, and produce defects such as pores and cracks inside the quartz tube during preparation, which seriously affects the quality of quartz tube. Although attaching a layer of photocatalyst to the inner wall of quartz tube avoids the impact on the quality of quartz tube, many attachment processes are simply coating and drying the inner wall of quartz tube, and the film layer is prone to fall off during operation. Summary of the invention
[0004] In order to solve the above technical defects, the present invention has developed a preparation process for high-quality quartz tubes, so that the prepared high-quality quartz tubes have high purity, the mechanical strength and quality of the quartz tubes are improved, and the photocatalytic film layer attached to the inner wall of the quartz tube by electrolysis also has excellent stability and photocatalytic performance when working.
[0005] A preparation process of a high-quality quartz tube comprises the following steps:
[0006] S1: Shot peening and acid leaching of quartz sand combined with impurity removal,
[0007] The quartz ore is crushed and soaked in a mixed acid of HCl, HNO3 and HF, then rinsed with clean water and dried, quartz ore particles with opaque impurities are selected to obtain cleaned quartz ore particles, the cleaned quartz ore particles are further crushed to obtain quartz ore particles, the quartz ore particles are calcined and placed in a high-temperature shot peening machine for shot peening, the quartz ore particles hit on a receiving plate under the action of the high-temperature shot peening machine and then fall into low-temperature deionized water for water quenching, taken out and dried to obtain quartz sand, the quartz sand is subjected to magnetic separation and flotation to obtain impurity-removed quartz sand, the impurity-removed quartz sand is immersed in a pickling agent, heated and allowed to stand, rinsed with deionized water and dried to obtain acid-leached quartz sand, the acid-leached quartz sand is subjected to chlorination roasting and then cooled to room temperature in nitrogen to obtain high-purity quartz sand;
[0008] S2: Melting, drawing and inner wall coating of quartz tube,
[0009] The high-purity quartz sand is liquefied and passed into a vertical tube drawing machine to be drawn into a rough quartz tube, which is then cut, the inner wall is polished and cleaned to obtain a high-purity quartz tube, a polyvinylidene fluoride solution is prepared, the polyvinylidene fluoride solution is coated on the inner wall of the quartz tube by a spin coating method, and the inner wall modified quartz tube is obtained after drying, black phosphorus powder and acetonitrile are mixed and then heated in an oil bath under a nitrogen atmosphere to obtain a black phosphorus dispersion, 4-azidobenzoic acid is added to the black phosphorus dispersion, and the oil bath is continuously heated in a nitrogen atmosphere to obtain a passivated black phosphorus dispersion, the inner wall modified quartz tube is completely immersed in the passivated black phosphorus dispersion, the surface is rinsed after standing, and then dried to obtain an inner wall coated quartz tube;
[0010] S3: Photosensitive treatment of the inner wall of the quartz tube with inner wall coating,
[0011] An adjustable DC regulated power supply is prepared, and cobalt sheets and molybdenum sheets are used as anodes, which are pasted on the inner wall of the inner wall coated quartz tube with a wire, and the inner wall of the inner wall coated quartz tube is used as a cathode. Then, both the anode and the cathode are immersed in an electrolyte solvent, and the container is sealed and the voltage is adjusted to perform electrolysis to obtain a quartz tube with a composite material deposited on the inner wall. The outer wall is rinsed and heated, and the quartz tube with the composite material deposited on the inner wall is rinsed with a propylene carbonate solution and anhydrous ethanol in turn, and a high-quality quartz tube is obtained after drying.
[0012] Furthermore, the step S1 of shot peening and acid leaching of quartz sand combined with impurity removal comprises the following steps:
[0013] S1.1: Place the quartz ore in a jaw crusher and crush it into small pieces of 1-5 cm to obtain quartz ore particles. Soak the quartz ore particles in a mixed acid of HCl, HNO3 and HF with a volume ratio of 1: (0.4-0.5): (0.2-0.3) for 20-24 hours, then rinse with clean water and dry, select the quartz ore particles with opaque impurities, and obtain cleaned quartz ore particles;
[0014] S1.2: The cleaned quartz ore particles are placed in a roller mill for further crushing, and quartz ore particles of 200-500 μm are obtained through a mesh sieve. The quartz ore particles are placed in a high-temperature furnace, and the temperature of the high-temperature furnace is adjusted to 800-850°C for calcination for 4-5 minutes. After the calcination is completed, the quartz ore particles are quickly placed in a high-temperature shot peening machine, and the shot peening impact angle is adjusted to 90°, the input current is 30-40A, the distance between the nozzle and the receiving plate is 30-40cm, and the receiving plate is placed vertically. A receiving container filled with deionized water at a temperature of 10-20°C is placed under the receiving plate. At this time, the high-temperature shot peening machine is started. When the quartz ore particles hit the receiving plate under the action of the high-temperature shot peening machine, they immediately fall into the receiving container filled with deionized water at a temperature of 10-20°C for water quenching, and are taken out and dried to obtain quartz sand;
[0015] S1.3: Place quartz sand in a magnetic separator for magnetic separation to adsorb magnetic impurities, and then enter a flotation machine for flotation to obtain impurity-free quartz sand. Mix the impurity-free quartz sand and the pickling agent at a solid-liquid ratio of 1: (0.3-0.4) and put them into a Teflon sealed can. Then heat the Teflon sealed can to 60-80°C in a water bath, keep the temperature and let it stand for 3-4 hours, then rinse it with deionized water and dry it to obtain acid-leached quartz sand. Place the acid-leached quartz sand in a double-pass quartz glass tube, continuously introduce HCl gas, set the gas flow rate to 3-4L / min, and heat to 900-1000°C for 6-8 minutes of roasting, then replace the introduced HCl gas with introduced nitrogen and stop heating, cool it to room temperature in nitrogen to obtain high-purity quartz sand.
[0016] Furthermore, step S2 of melting, drawing and inner wall coating of the quartz tube comprises the following steps:
[0017] S2.1: Add high-purity quartz sand to a crucible, then place it in a high-temperature boiler, heat it at a temperature of 2000-2400°C, until the high-purity quartz sand is completely liquefied to obtain a quartz melt, pass the quartz melt into a vertical tube drawing machine, and draw it into a rough quartz tube at a drawing speed of 0.3-0.5mm / min, then use a cutting device to cut the rough quartz tube to control the length to 1.5-2.5m, and then use a grinder to grind the inner wall of the quartz tube to ensure the integrity of the inner wall of the quartz tube while controlling the mesh number of the inner wall of the quartz tube to 600-900 meshes, rinse it with clean water, rinse it with hydrochloric acid solution for 2-3 minutes, and then rinse it with clean water to obtain a high-purity quartz tube;
[0018] S2.2: Dissolve polyvinylidene fluoride in N-methylpyrrolidone to prepare a polyvinylidene fluoride solution with a mass fraction of 10-15%. Fix the high-purity quartz tube on a rotating device, and then coat the polyvinylidene fluoride solution on the inner wall of the high-purity quartz tube by spin coating. The coating amount is 0.8-1mL / cm 2 , and then placed in a drying oven at a temperature of 70-80°C for drying, and then continuously introduced oxygen plasma gas flow into the high-purity quartz tube through a plasma device, with a gas flow rate of 40-50sccm, to obtain an inner wall modified quartz tube;
[0019] S2.3: Place black phosphorus powder and acetonitrile in a gas-filled reactor at a mass ratio of 1:(2-3), charge and discharge nitrogen 4-5 times, and then heat in an oil bath at 200-220°C for 20-24 hours under a nitrogen atmosphere to obtain a black phosphorus dispersion, and then add 8-10wt% of 4-azidobenzoic acid to the black phosphorus dispersion, and continue to heat in an oil bath at 150-160°C for 40-48 hours under a nitrogen atmosphere to obtain a passivated black phosphorus dispersion, completely immerse the inner wall modified quartz tube in the passivated black phosphorus dispersion, stand at 100-140°C for 8-10 hours, rinse the surface with deionized water, and then dry in a vacuum drying oven at 40-45°C for 18-20 hours to obtain an inner wall coated quartz tube.
[0020] Furthermore, in step S3, the photosensitivity treatment of the inner wall of the inner wall coating quartz tube comprises the following steps:
[0021] S3.1: prepare an adjustable DC regulated power supply, use a cobalt sheet and a molybdenum sheet as an anode, use a wire to stick them on the inner wall of the inner wall coated quartz tube, use the inner wall of the inner wall coated quartz tube as a cathode, then immerse both the anode and the cathode in an electrolyte solvent, seal the container and adjust the voltage of the adjustable DC regulated power supply to 35-40V, perform electrolysis for 2-3 hours, and obtain a quartz tube with a composite material deposited on the inner wall;
[0022] S3.2: Rinse the outer wall of the quartz tube with the composite material deposited on the inner wall with deionized water, and then heat it in a vacuum drying oven at 160-180°C for 3-4 hours. Rinse the quartz tube with the composite material deposited on the inner wall with propylene carbonate solution and anhydrous ethanol for 2-3 times, and then dry it in a vacuum drying oven at 60-70°C for 6-8 hours to obtain a high-quality quartz tube.
[0023] Furthermore, in step S1.2, the shot blasting wheel of the high temperature resistant shot blasting machine is coated with alumina ceramics, the inner lining plate is an alumina ceramic plate, and the nozzle, the conveying pipeline and the feeding system are all made of high temperature resistant Inconel600 alloy.
[0024] Furthermore, the receiving plate in step S1.2 is a marble plate.
[0025] Furthermore, the flotation process of step S1.3 is to first adjust the pH of the pulp to 3-4 with 5-6% sulfuric acid, float mica with polyetheramine, and finally adjust the pH to 2-3 with 8-10% hydrofluoric acid, float feldspar with polyetheramine, and quartz is produced in the form of tailings.
[0026] Furthermore, in step S1.3, the pickling agent is prepared by sulfuric acid with a concentration of 20-25% and hydrofluoric acid with a concentration of 18-20% in a volume ratio of 1:1.
[0027] Furthermore, the concentration of the hydrochloric acid solution in step S2.1 is 10-20%.
[0028] Furthermore, the electrolyte solvent in step S3.1 is a mixed solution of propylene carbonate containing 0.6-0.8 mol / L of TBABF4.
[0029] The beneficial effects are as follows: 1. The present invention places quartz ore particles in a high-temperature furnace for high-temperature calcination, and then quickly places the quartz ore particles after calcination in a high-temperature shot peening machine for shot peening. A vertical receiving plate is arranged in front of the nozzle so that the quartz ore particles collide with the receiving plate at high speed under the action of the high-temperature shot peening machine. At this time, the quartz ore particles that have rapidly expanded after calcination break along crystal defects and grain boundaries under the action of the impact, exposing impurities in the internal inclusions of the quartz and element impurities in the internal cracks of the quartz. After the impact, the high-temperature quartz ore particles fall into water for water quenching, which rapidly increases the internal stress of the ore, further causing the quartz ore particles to break along the crystal, fully exposing the impurities in the internal inclusions of the quartz, so that the subsequent acid leaching treatment can better remove these impurities, thereby greatly improving the purity of the obtained high-purity quartz sand and improving the mechanical strength and quality of the subsequently prepared quartz tube.
[0030] 2. The present invention prepares a high-purity quartz tube and uses a spin coating method at 0.8-1 mL / cm 2A layer of polyvinylidene fluoride solution is coated on the inner wall of a high-purity quartz tube with a coating amount, and the inner wall is treated with oxygen plasma after drying. This can not only improve the conductivity of the inner wall of the subsequent inner wall coating quartz tube, so that the electrolysis can be carried out better, and a uniform and dense photosensitive composite material can be formed on the inner wall, but the oxygen plasma can also introduce hydroxyl groups on the surface of the polyvinylidene fluoride film, so that the passivated black phosphorus dispersion grows on the surface of the polyvinylidene fluoride film, and the black phosphorus is tightly combined with the inner wall of the quartz tube, which provides a basis for the stability and density of the subsequent photosensitive composite material, thereby improving the photocatalytic performance of high-quality quartz tubes.
[0031] 3. The present invention uses cobalt sheets and molybdenum sheets as anodes and the inner wall of the inner-wall coated quartz tube as cathode, and then immerses it in an electrolyte solvent for electrolysis. The black phosphorus on the inner wall of the inner-wall coated quartz tube combines with the cobalt ions and molybdenum ions obtained by electrolysis to form a cobalt oxide-molybdenum oxide-black phosphorus composite material, so that the high-quality quartz tube has efficient photocatalytic performance, greatly improving the effect of photocatalytic degradation of organic compounds under visible light or ultraviolet light radiation, and the cobalt oxide-molybdenum oxide-black phosphorus composite material prepared by this electrolysis method has a strong adhesion ability to the inner wall of the quartz tube, and can stably perform photocatalytic operations. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a process flow chart for preparing the high-quality quartz tube used in the embodiments of the present invention. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] A process for preparing high quality quartz tubes, such as Figure 1 As shown, the following steps are included:
[0036] S1: Shot peening and acid leaching of quartz sand combined with impurity removal
[0037] S1.1: crushing the quartz ore into small pieces of 1 cm in a jaw crusher to obtain quartz ore particles, soaking the quartz ore particles in a mixed acid of HCl, HNO3 and HF in a volume ratio of 1:0.4:0.2 for 20 hours, then rinsing with clean water and drying, selecting the quartz ore particles with opaque impurities to obtain cleaned quartz ore particles;
[0038] S1.2: The cleaned quartz ore particles are placed in a roller mill for further crushing, and quartz ore particles of 200 μm are obtained through a mesh sieve. The quartz ore particles are placed in a high-temperature furnace, and the temperature of the high-temperature furnace is adjusted to 800°C for calcination for 4 minutes. After the calcination is completed, the quartz ore particles are quickly placed in a high-temperature shot peening machine, and the shot peening impact angle is adjusted to 90°, the input current is 30A, the distance between the nozzle and the marble plate receiving plate is 30 cm, and the marble plate receiving plate is placed vertically. A receiving container filled with deionized water at a temperature of 10°C is placed under the marble plate receiving plate. At this time, the high-temperature shot peening machine is started. When the quartz ore particles hit the receiving plate under the action of the high-temperature shot peening machine, they immediately fall into the receiving container filled with deionized water at a temperature of 10°C for water quenching, and are taken out and dried to obtain quartz sand;
[0039] S1.3: Place the quartz sand in a magnetic separator for magnetic separation to adsorb magnetic impurities, and then enter the flotation machine for flotation. First, adjust the pulp pH to 3 with 5% sulfuric acid, use polyetheramine to float mica, and finally adjust the pH to 2 with 8% hydrofluoric acid, use polyetheramine to float feldspar, and quartz is produced in the form of tailings to obtain impurity-free quartz sand. The impurity-free quartz sand and the pickling agent are mixed in a Teflon sealed tank at a solid-liquid ratio of 1:0.3. The pickling agent is composed of 20% sulfuric acid and 18% hydrofluoric acid. The acid is prepared in a volume ratio of 1:1, and then the Teflon sealed tank is heated to 60°C in a water bath, the temperature is maintained and allowed to stand for 3 hours, and then rinsed with deionized water and dried to obtain acid-leached quartz sand. The acid-leached quartz sand is placed in a double-pass quartz glass tube, HCl gas is continuously introduced, the gas flow rate is set to 3L / min, and heated to 900°C for 6 minutes of roasting, and then the HCl gas is replaced by nitrogen and the heating is stopped, and it is cooled to room temperature in nitrogen to obtain high-purity quartz sand.
[0040] S2: Melting, drawing and inner wall coating of quartz tube
[0041] S2.1: Add high-purity quartz sand to a crucible, and then place it in a high-temperature boiler and heat it at a temperature of 2000°C until the high-purity quartz sand is completely liquefied to obtain a quartz melt, and pass the quartz melt into a vertical tube drawing machine, and draw it into a rough quartz tube at a drawing speed of 0.3 mm / min, and then use a cutting device to cut the rough quartz tube to control the length to 1.5 m, and then use a grinder to grind the inner wall of the quartz tube to ensure the integrity of the inner wall of the quartz tube while controlling the mesh number of the inner wall of the quartz tube to 600 meshes, rinse it with clean water, rinse it with a 10% hydrochloric acid solution for 2 minutes, and then rinse it with clean water to obtain a high-purity quartz tube;
[0042] S2.2: Dissolve polyvinylidene fluoride in N-methylpyrrolidone to prepare a polyvinylidene fluoride solution with a mass fraction of 10%. Fix the high-purity quartz tube on a rotating device, and then coat the polyvinylidene fluoride solution on the inner wall of the quartz tube by spin coating. The coating amount is 0.8mL / cm 2 , and then placed in a drying oven at a temperature of 70°C for drying, and then continuously introduced oxygen plasma gas flow into the quartz tube through a plasma device, with a gas flow rate of 40 sccm, to obtain an inner wall modified quartz tube;
[0043] S2.3: Black phosphorus powder and acetonitrile are placed in a gas-filled reactor in a mass ratio of 1:2, and nitrogen is charged and discharged 4 times. Then, the reactor is heated in an oil bath at 200°C for 20 hours under a nitrogen atmosphere to obtain a black phosphorus dispersion. Then, 8 wt% of 4-azidobenzoic acid is added to the black phosphorus dispersion. The reactor is further heated in an oil bath at 150°C for 40 hours under a nitrogen atmosphere to obtain a passivated black phosphorus dispersion. The inner wall modified quartz tube is completely immersed in the passivated black phosphorus dispersion. After standing at 100°C for 8 hours, the surface is rinsed with deionized water. The tube is then dried in a vacuum drying oven at 40°C for 18 hours to obtain an inner wall coated quartz tube.
[0044] S3: Photosensitive treatment of the inner wall of the quartz tube with inner wall coating
[0045] S3.1: prepare an adjustable DC regulated power supply, use cobalt and molybdenum sheets as anodes, use wires to stick them on the inner wall of the inner wall coated quartz tube, use the inner wall of the inner wall coated quartz tube as the cathode, then immerse both the anode and the cathode in a propylene carbonate mixed solution containing 0.6 mol / L tbABF4, seal the container and adjust the voltage of the adjustable DC regulated power supply to 35 V, perform electrolysis for 2 hours, and obtain a quartz tube with a composite material deposited on the inner wall;
[0046] S3.2: Rinse the outer wall of the quartz tube with the composite material deposited on the inner wall with deionized water, and then heat it in a vacuum drying oven at 160°C for 3 hours. Rinse the quartz tube with the composite material deposited on the inner wall twice with propylene carbonate solution and anhydrous ethanol in turn, and then dry it in a vacuum drying oven at 60°C for 6 hours to obtain a high-quality quartz tube.
[0047] Example 2
[0048] A process for preparing high quality quartz tubes, such as Figure 1 As shown, the following steps are included:
[0049] S1: Shot peening and acid leaching of quartz sand combined with impurity removal
[0050] S1.1: crushing the quartz ore into small pieces of 1 cm in a jaw crusher to obtain quartz ore particles, soaking the quartz ore particles in a mixed acid of HCl, HNO3 and HF in a volume ratio of 1:0.4:0.2 for 20 hours, then rinsing with clean water and drying, selecting the quartz ore particles with opaque impurities to obtain cleaned quartz ore particles;
[0051] S1.2: The cleaned quartz ore particles are placed in a roller mill for further crushing, and quartz ore particles of 200 μm are obtained through a mesh sieve. The quartz ore particles are placed in a high-temperature furnace, and the temperature of the high-temperature furnace is adjusted to 800°C for calcination for 4 minutes. After the calcination is completed, the quartz ore particles are quickly placed in a high-temperature shot peening machine, and the shot peening impact angle is adjusted to 90°, the input current is 30A, the distance between the nozzle and the marble plate receiving plate is 30 cm, and the marble plate receiving plate is placed vertically. A receiving container filled with deionized water at a temperature of 10°C is placed under the marble plate receiving plate. At this time, the high-temperature shot peening machine is started. When the quartz ore particles hit the receiving plate under the action of the high-temperature shot peening machine, they immediately fall into the receiving container filled with deionized water at a temperature of 10°C for water quenching, and are taken out and dried to obtain quartz sand;
[0052] S1.3: Place the quartz sand in a magnetic separator for magnetic separation to absorb magnetic impurities, and then enter the flotation machine for flotation. First, adjust the pulp pH to 3 with 5% sulfuric acid, use polyetheramine to float mica, and finally adjust the pH to 2 with 8% hydrofluoric acid, use polyetheramine to float feldspar, and the quartz is produced in the form of tailings to obtain impurity-free quartz sand. The impurity-free quartz sand and the pickling agent are mixed in a Teflon sealed tank at a solid-liquid ratio of 1:0.4. The pickling agent is composed of 20% sulfuric acid and 18% hydrofluoric acid. The acid is prepared in a volume ratio of 1:1, and then the Teflon sealed tank is heated to 60°C in a water bath, the temperature is maintained and allowed to stand for 3 hours, and then rinsed with deionized water and dried to obtain acid-leached quartz sand. The acid-leached quartz sand is placed in a double-pass quartz glass tube, HCl gas is continuously introduced, the gas flow rate is set to 3L / min, and heated to 900°C for 6 minutes of roasting, and then the HCl gas is replaced by nitrogen and the heating is stopped, and it is cooled to room temperature in nitrogen to obtain high-purity quartz sand.
[0053] S2: Melting, drawing and inner wall coating of quartz tube
[0054] S2.1: Add high-purity quartz sand to a crucible, and then place it in a high-temperature boiler and heat it at a temperature of 2000°C until the high-purity quartz sand is completely liquefied to obtain a quartz melt, and pass the quartz melt into a vertical tube drawing machine, and draw it into a rough quartz tube at a drawing speed of 0.3 mm / min, and then use a cutting device to cut the rough quartz tube to control the length to 1.5 m, and then use a grinder to grind the inner wall of the quartz tube to ensure the integrity of the inner wall of the quartz tube while controlling the mesh number of the inner wall of the quartz tube to 600 meshes, rinse it with clean water, rinse it with a 10% hydrochloric acid solution for 2 minutes, and then rinse it with clean water to obtain a high-purity quartz tube;
[0055] S2.2: Dissolve polyvinylidene fluoride in N-methylpyrrolidone to prepare a polyvinylidene fluoride solution with a mass fraction of 15%. Fix a high-purity quartz tube on a rotating device, and then coat the polyvinylidene fluoride solution on the inner wall of the quartz tube by spin coating. The coating amount is 1 mL / cm 2 , and then placed in a drying oven at a temperature of 70°C for drying, and then continuously introduced oxygen plasma gas flow into the quartz tube through a plasma device, with a gas flow rate of 40 sccm, to obtain an inner wall modified quartz tube;
[0056] S2.3: Black phosphorus powder and acetonitrile are placed in a gas-filled reactor in a mass ratio of 1:3, and nitrogen is charged and discharged four times. Then, the reactor is heated in an oil bath at 200°C for 20 hours under a nitrogen atmosphere to obtain a black phosphorus dispersion. Then, 10 wt% of 4-azidobenzoic acid is added to the black phosphorus dispersion. The reactor is further heated in an oil bath at 150°C for 40 hours under a nitrogen atmosphere to obtain a passivated black phosphorus dispersion. The inner wall modified quartz tube is completely immersed in the passivated black phosphorus dispersion. After standing at 100°C for 8 hours, the surface is rinsed with deionized water. The tube is then dried in a vacuum drying oven at 40°C for 18 hours to obtain an inner wall coated quartz tube.
[0057] S3: Photosensitive treatment of the inner wall of the quartz tube with inner wall coating
[0058] S3.1: prepare an adjustable DC regulated power supply, use cobalt and molybdenum sheets as anodes, use wires to stick them on the inner wall of the inner wall coated quartz tube, use the inner wall of the inner wall coated quartz tube as the cathode, then immerse both the anode and the cathode in a propylene carbonate mixed solution containing 0.6 mol / L tbABF4, seal the container and adjust the voltage of the adjustable DC regulated power supply to 35 V, perform electrolysis for 2 hours, and obtain a quartz tube with a composite material deposited on the inner wall;
[0059] S3.2: Rinse the outer wall of the quartz tube with the composite material deposited on the inner wall with deionized water, and then heat it in a vacuum drying oven at 160°C for 3 hours. Rinse the quartz tube with the composite material deposited on the inner wall twice with propylene carbonate solution and anhydrous ethanol in turn, and then dry it in a vacuum drying oven at 60°C for 6 hours to obtain a high-quality quartz tube.
[0060] Example 3
[0061] A process for preparing high quality quartz tubes, such as Figure 1 As shown, the following steps are included:
[0062] S1: Shot peening and acid leaching of quartz sand combined with impurity removal
[0063] S1.1: crushing the quartz ore into 5 cm small pieces in a jaw crusher to obtain quartz ore particles, soaking the quartz ore particles in a mixed acid of HCl, HNO3 and HF in a volume ratio of 1:0.5:0.3 for 24 hours, then rinsing with clean water and drying, selecting the quartz ore particles with opaque impurities to obtain cleaned quartz ore particles;
[0064] S1.2: The cleaned quartz ore particles are placed in a roller mill for further crushing, and quartz ore particles of 500 μm are obtained through a mesh sieve. The quartz ore particles are placed in a high-temperature furnace, and the temperature of the high-temperature furnace is adjusted to 850°C for calcination for 5 minutes. After the calcination is completed, the quartz ore particles are quickly placed in a high-temperature shot peening machine, and the shot peening impact angle is adjusted to 90°, the input current is 40A, the distance between the nozzle and the marble plate receiving plate is 40 cm, and the marble plate receiving plate is placed vertically. A receiving container filled with deionized water at a temperature of 20°C is placed under the marble plate receiving plate. At this time, the high-temperature shot peening machine is started. When the quartz ore particles hit the receiving plate under the action of the high-temperature shot peening machine, they immediately fall into the receiving container filled with deionized water at a temperature of 20°C for water quenching, and are taken out and dried to obtain quartz sand;
[0065] S1.3: Place the quartz sand in a magnetic separator for magnetic separation to adsorb magnetic impurities, and then put it into a flotation machine for flotation. First, adjust the pH of the pulp to 4 with 6% sulfuric acid, use polyetheramine to float mica, and finally adjust the pH to 3 with 10% hydrofluoric acid, use polyetheramine to float feldspar, and the quartz is produced in the form of tailings to obtain impurity-free quartz sand. The impurity-free quartz sand and the pickling agent are mixed in a Teflon sealed tank at a solid-liquid ratio of 1:0.4. The pickling agent is composed of 25% sulfuric acid and 20% hydrofluoric acid. The acid is prepared in a volume ratio of 1:1, and then the Teflon sealed tank is heated to 80°C in a water bath, the temperature is maintained and allowed to stand for 4 hours, and then it is rinsed with deionized water and dried to obtain acid-leached quartz sand. The acid-leached quartz sand is placed in a double-pass quartz glass tube, HCl gas is continuously introduced, the gas flow rate is set to 4L / min, and it is heated to 1000°C for 8 minutes of roasting, and then the HCl gas is replaced by nitrogen gas and the heating is stopped, and it is cooled to room temperature in nitrogen to obtain high-purity quartz sand.
[0066] S2: Melting, drawing and inner wall coating of quartz tube
[0067] S2.1: Add high-purity quartz sand to a crucible, and then place it in a high-temperature boiler and heat it at a temperature of 2400°C until the high-purity quartz sand is completely liquefied to obtain a quartz melt, and pass the quartz melt into a vertical tube drawing machine, and draw it into a rough quartz tube at a drawing speed of 0.5 mm / min, and then use a cutting device to cut the rough quartz tube to control the length to 2.5 m, and then use a grinder to grind the inner wall of the quartz tube to ensure the integrity of the inner wall of the quartz tube while controlling the mesh number of the inner wall of the quartz tube to 900 meshes, rinse it with clean water, rinse it with a 20% hydrochloric acid solution for 3 minutes, and then rinse it with clean water to obtain a high-purity quartz tube;
[0068] S2.2: Dissolve polyvinylidene fluoride in N-methylpyrrolidone to prepare a polyvinylidene fluoride solution with a mass fraction of 15%. Fix the high-purity quartz tube on a rotating device, and then coat the polyvinylidene fluoride solution on the inner wall of the quartz tube by spin coating. The coating amount is 0.8mL / cm 2 , and then placed in a drying oven at a temperature of 80°C for drying, and then continuously introduced oxygen plasma gas flow into the quartz tube through a plasma device, with a gas flow rate of 50 sccm, to obtain an inner wall modified quartz tube;
[0069] S2.3: Black phosphorus powder and acetonitrile are placed in a gas-filled reactor in a mass ratio of 1:2, and nitrogen is charged and discharged for 5 times. Then, the reactor is heated in an oil bath at 220°C for 24 hours under a nitrogen atmosphere to obtain a black phosphorus dispersion. Then, 8 wt% of 4-azidobenzoic acid is added to the black phosphorus dispersion. The reactor is further heated in an oil bath at 160°C for 48 hours under a nitrogen atmosphere to obtain a passivated black phosphorus dispersion. The inner wall modified quartz tube is completely immersed in the passivated black phosphorus dispersion. After standing at 140°C for 10 hours, the surface is rinsed with deionized water. The tube is then dried in a vacuum drying oven at 45°C for 20 hours to obtain an inner wall coated quartz tube.
[0070] S3: Photosensitive treatment of the inner wall of the quartz tube with inner wall coating
[0071] S3.1: prepare an adjustable DC regulated power supply, use cobalt and molybdenum sheets as anodes, use wires to stick them on the inner wall of the inner wall coated quartz tube, use the inner wall of the inner wall coated quartz tube as the cathode, then immerse both the anode and the cathode in a propylene carbonate mixed solution containing 0.8 mol / L tbABF4, seal the container and adjust the voltage of the adjustable DC regulated power supply to 40 V, perform electrolysis for 3 hours, and obtain a quartz tube with a composite material deposited on the inner wall;
[0072] S3.2: Rinse the outer wall of the quartz tube with the composite material deposited on the inner wall with deionized water, and then heat it in a vacuum drying oven at 180°C for 4 hours. Rinse the quartz tube with the composite material deposited on the inner wall with propylene carbonate solution and anhydrous ethanol three times in turn, and then dry it in a vacuum drying oven at 70°C for 8 hours to obtain a high-quality quartz tube.
[0073] Comparative Example 1
[0074] Compared with Example 1, the difference of Comparative Example 1 is that Comparative Example 1 removes the step of placing the quartz ore particles in a high-temperature resistant shot peening machine for shot peening in step S1.2, and directly water quenches the quartz ore particles after calcination, and the remaining steps are the same as Example 1.
[0075] Comparative Example 2
[0076] Compared with Example 1, the difference of Comparative Example 2 is that in step S2.2, oxygen plasma gas flow is not continuously introduced into the high-purity quartz tube in Comparative Example 2, and the remaining steps are the same as those in Example 1. The obtained high-quality quartz tube is recorded as Comparative Example 2.
[0077] Comparative Example 3
[0078] Compared with Example 1, the difference of Comparative Example 3 is that step S3 is removed in Comparative Example 3, and the remaining steps are the same as those in Example 1. The obtained inner wall coated quartz tube is recorded as Comparative Example 3.
[0079] Experiment 1: Take the same batch of quartz ore with uniform impurity distribution, and prepare them into quartz particles by the process of Example 1. Then take the same mass of quartz particles and prepare them into high-purity quartz sand by the example and two portions of comparative example 1. Prepare high-purity quartz sand, and use ICP-MS to characterize and measure the content of metal impurities in the quartz particles and high-purity quartz sand. Record the data and make a table, as shown in Table 1. It can be seen that the metal impurity content of the high-purity quartz sand prepared in Examples 1-3 is less than that of the high-purity quartz sand prepared in Comparative Example 1. It can be proved that the quartz ore particles after calcination are quickly shot peened to collide with the receiving plate, so that the impurities in the inclusions inside the quartz and the element impurities in the internal cracks can be exposed, so that the subsequent acid leaching treatment can better remove these impurities, thereby greatly improving the purity of the obtained high-purity quartz sand.
[0080] Experiment 2: Take the high-quality quartz tubes prepared in the embodiment and comparative examples 2-3 of the same mass, place them in a 15 ppm MB (methylene blue) solution, degrade MB for 60 minutes under visible light, repeat 8 times, record the degradation rate of MB each time, record the data and make a table, as shown in Table 2, it can be seen that the degradation rate of MB in the high-quality quartz tube prepared in the embodiment is greater than the first degradation rate of comparative examples 2-3, which can prove that the treatment of the high-purity quartz tube with oxygen plasma gas flow can improve the photocatalytic performance of the high-quality quartz tube, and it can also be proved that the cobalt sheet and the molybdenum sheet are used as the anode, the inner wall of the inner wall coated quartz tube is used as the cathode, and then immersed in the electrolyte solvent for electrolysis, and a cobalt oxide-molybdenum oxide-black phosphorus composite material is formed on the inner wall of the quartz tube, which can make the high-quality quartz tube have efficient photocatalytic performance;
[0081] It can also be seen from Table 2 that with the increase in the number of repetitions, the decrease in the MB degradation rate of the high-quality quartz tube prepared in the embodiment is much smaller than the decrease in the MB degradation rate of comparative examples 2-3, indicating that the photocatalytic stability of the high-quality quartz tube prepared in the embodiment is higher than that of comparative examples 2-3. It can be proved that the treatment of the high-purity quartz tube with oxygen plasma gas flow can improve the photocatalytic stability of the high-quality quartz tube. It can also be proved that using cobalt sheets and molybdenum sheets as anodes, the inner wall of the inner wall coated quartz tube as a cathode, and then immersing it in an electrolyte solvent for electrolysis, forming a cobalt oxide-molybdenum oxide-black phosphorus composite material on the inner wall of the quartz tube, can enhance the stability of the photocatalytic operation of the high-quality quartz tube.
[0082] Table 1: Metal impurity content of high purity quartz sand
[0083]
[0084] Table 2: Degradation rate of MB by high quality quartz tube
[0085]
[0086] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A process for preparing a high-quality quartz tube, characterized in that: The following steps are involved: S1: Shot peening and acid leaching of quartz sand combined with impurity removal, The quartz ore is crushed and soaked in a mixed acid of HCl, HNO3 and HF, then rinsed with clean water and dried, quartz ore particles with opaque impurities are selected to obtain cleaned quartz ore particles, the cleaned quartz ore particles are further crushed to obtain quartz ore particles, the quartz ore particles are calcined and placed in a high-temperature shot peening machine for shot peening, the quartz ore particles hit on a receiving plate under the action of the high-temperature shot peening machine and then fall into low-temperature deionized water for water quenching, taken out and dried to obtain quartz sand, the quartz sand is subjected to magnetic separation and flotation to obtain impurity-removed quartz sand, the impurity-removed quartz sand is immersed in a pickling agent, heated and allowed to stand, rinsed with deionized water and dried to obtain acid-leached quartz sand, the acid-leached quartz sand is subjected to chlorination roasting and then cooled to room temperature in nitrogen to obtain high-purity quartz sand; S2: Melting, drawing and inner wall coating of quartz tube, The high-purity quartz sand is liquefied and passed into a vertical tube drawing machine to be drawn into a rough quartz tube, which is then cut, the inner wall is polished and cleaned to obtain a high-purity quartz tube, a polyvinylidene fluoride solution is prepared, the polyvinylidene fluoride solution is coated on the inner wall of the quartz tube by a spin coating method, and the inner wall modified quartz tube is obtained after drying, black phosphorus powder and acetonitrile are mixed and then heated in an oil bath under a nitrogen atmosphere to obtain a black phosphorus dispersion, 4-azidobenzoic acid is added to the black phosphorus dispersion, and the oil bath is continuously heated in a nitrogen atmosphere to obtain a passivated black phosphorus dispersion, the inner wall modified quartz tube is completely immersed in the passivated black phosphorus dispersion, the surface is rinsed after standing, and then dried to obtain an inner wall coated quartz tube; S3: Photosensitive treatment of the inner wall of the quartz tube with inner wall coating, An adjustable DC regulated power supply is prepared, and cobalt sheets and molybdenum sheets are used as anodes, which are pasted on the inner wall of the inner wall coated quartz tube with a wire, and the inner wall of the inner wall coated quartz tube is used as a cathode. Then, both the anode and the cathode are immersed in an electrolyte solvent, and the container is sealed and the voltage is adjusted to perform electrolysis to obtain a quartz tube with a composite material deposited on the inner wall. The outer wall is rinsed and heated, and the quartz tube with the composite material deposited on the inner wall is rinsed with a propylene carbonate solution and anhydrous ethanol in turn, and a high-quality quartz tube is obtained after drying.
2. The process for preparing a high-quality quartz tube according to claim 1, characterized in that: Step S1: Shot peening and acid leaching of quartz sand combined with impurity removal, comprising the following steps: S1.1: Place the quartz ore in a jaw crusher and crush it into small pieces of 1-5 cm to obtain quartz ore particles. Soak the quartz ore particles in a mixed acid of HCl, HNO3 and HF with a volume ratio of 1: (0.4-0.5): (0.2-0.3) for 20-24 hours, then rinse with clean water and dry, select the quartz ore particles with opaque impurities, and obtain cleaned quartz ore particles; S1.2: The cleaned quartz ore particles are placed in a roller mill for further crushing, and quartz ore particles of 200-500 μm are obtained through a mesh sieve. The quartz ore particles are placed in a high-temperature furnace, and the temperature of the high-temperature furnace is adjusted to 800-850°C for calcination for 4-5 minutes. After the calcination is completed, the quartz ore particles are quickly placed in a high-temperature shot peening machine, and the shot peening impact angle is adjusted to 90°, the input current is 30-40A, the distance between the nozzle and the receiving plate is 30-40cm, and the receiving plate is placed vertically. A receiving container filled with deionized water at a temperature of 10-20°C is placed under the receiving plate. At this time, the high-temperature shot peening machine is started. When the quartz ore particles hit the receiving plate under the action of the high-temperature shot peening machine, they immediately fall into the receiving container filled with deionized water at a temperature of 10-20°C for water quenching, and are taken out and dried to obtain quartz sand; S1.3: Place quartz sand in a magnetic separator for magnetic separation to adsorb magnetic impurities, and then enter a flotation machine for flotation to obtain impurity-free quartz sand. Mix the impurity-free quartz sand and the pickling agent at a solid-liquid ratio of 1: (0.3-0.4) and put them into a Teflon sealed can. Then heat the Teflon sealed can to 60-80°C in a water bath, keep the temperature and let it stand for 3-4 hours, then rinse it with deionized water and dry it to obtain acid-leached quartz sand. Place the acid-leached quartz sand in a double-pass quartz glass tube, continuously introduce HCl gas, set the gas flow rate to 3-4L / min, and heat to 900-1000°C for 6-8 minutes of roasting, then replace the introduced HCl gas with introduced nitrogen and stop heating, cool it to room temperature in nitrogen to obtain high-purity quartz sand.
3. The process for preparing a high-quality quartz tube according to claim 1, characterized in that: Step S2: melting, drawing and inner wall coating of the quartz tube, including the following steps: S2.1: Add high-purity quartz sand to a crucible, then place it in a high-temperature boiler, heat it at a temperature of 2000-2400°C, until the high-purity quartz sand is completely liquefied to obtain a quartz melt, pass the quartz melt into a vertical tube drawing machine, and draw it into a rough quartz tube at a drawing speed of 0.3-0.5mm / min, then use a cutting device to cut the rough quartz tube to control the length to 1.5-2.5m, and then use a grinder to grind the inner wall of the quartz tube to ensure the integrity of the inner wall of the quartz tube while controlling the mesh number of the inner wall of the quartz tube to 600-900 meshes, rinse it with clean water, rinse it with hydrochloric acid solution for 2-3 minutes, and then rinse it with clean water to obtain a high-purity quartz tube; S2.2: Dissolve polyvinylidene fluoride in N-methylpyrrolidone to prepare a polyvinylidene fluoride solution with a mass fraction of 10-15%. Fix a high-purity quartz tube on a rotating device, and then apply the polyvinylidene fluoride solution to the inner wall of the quartz tube by spin coating. The coating amount is 0.8-1mL / cm 2 , and then placed in a drying oven at a temperature of 70-80°C for drying, and then continuously introduced oxygen plasma gas flow into the quartz tube through a plasma device, with a gas flow rate of 40-50sccm, to obtain an inner wall modified quartz tube; S2.3: Place black phosphorus powder and acetonitrile in a gas-filled reactor at a mass ratio of 1:(2-3), charge and discharge nitrogen 4-5 times, and then heat in an oil bath at 200-220°C for 20-24 hours under a nitrogen atmosphere to obtain a black phosphorus dispersion, and then add 8-10wt% of 4-azidobenzoic acid to the black phosphorus dispersion, and continue to heat in an oil bath at 150-160°C for 40-48 hours under a nitrogen atmosphere to obtain a passivated black phosphorus dispersion, completely immerse the inner wall modified quartz tube in the passivated black phosphorus dispersion, stand at 100-140°C for 8-10 hours, rinse the surface with deionized water, and then dry in a vacuum drying oven at 40-45°C for 18-20 hours to obtain an inner wall coated quartz tube.
4. The process for preparing a high-quality quartz tube according to claim 1, characterized in that: Step S3: treating the inner wall of the inner wall coated quartz tube with photosensitivity, comprising the following steps: S3.1: prepare an adjustable DC regulated power supply, use a cobalt sheet and a molybdenum sheet as an anode, use a wire to stick them on the inner wall of the inner wall coated quartz tube, use the inner wall of the inner wall coated quartz tube as a cathode, then immerse both the anode and the cathode in an electrolyte solvent, seal the container and adjust the voltage of the adjustable DC regulated power supply to 35-40V, perform electrolysis for 2-3 hours, and obtain a quartz tube with a composite material deposited on the inner wall; S3.2: Rinse the outer wall of the quartz tube with the composite material deposited on the inner wall with deionized water, and then heat it in a vacuum drying oven at 160-180°C for 3-4 hours. Rinse the quartz tube with the composite material deposited on the inner wall with propylene carbonate solution and anhydrous ethanol for 2-3 times, and then dry it in a vacuum drying oven at 60-70°C for 6-8 hours to obtain a high-quality quartz tube.
5. The process for preparing a high-quality quartz tube according to claim 2, characterized in that: In step S1.2, the shot blasting wheel of the high temperature resistant shot blasting machine is coated with alumina ceramics, the inner lining plate is an alumina ceramic plate, and the nozzle, conveying pipeline and feeding system are all made of high temperature resistant Inconel600 alloy.
6. The process for preparing a high-quality quartz tube according to claim 2, characterized in that: The receiving plate in step S1.2 is a marble plate.
7. The process for preparing a high-quality quartz tube according to claim 2, characterized in that: The flotation process of step S1.3 is to first adjust the pH of the pulp to 3-4 with 5-6% sulfuric acid, float mica with polyetheramine, and finally adjust the pH to 2-3 with 8-10% hydrofluoric acid, float feldspar with polyetheramine, and quartz is produced in the form of tailings.
8. The process for preparing a high-quality quartz tube according to claim 2, characterized in that: In step S1.3, the pickling agent is prepared by sulfuric acid with a concentration of 20-25% and hydrofluoric acid with a concentration of 18-20% in a volume ratio of 1:
1.
9. The process for preparing a high-quality quartz tube according to claim 3, characterized in that: The concentration of the hydrochloric acid solution in step S2.1 is 10-20%.
10. The process for preparing a high-quality quartz tube according to claim 4, characterized in that: The electrolyte solvent in step S3.1 is a mixed solution of propylene carbonate containing 0.6-0.8 mol / L of TBABF4.
Citation Information
Patent Citations
Rotating pipe and manufacturing method thereof
CN101265016A
Quartz tube protection method
CN104250726A